KOMUNIKASI DAKWAH DALAM BIMBINGAN SOSIAL MENUMBUHKAN KEMAMPUAN ADAPTASI MAD’U - Nurwahida Alimuddin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2014)
This paper argued that da’wah activities in social counseling foster adaptability of students in school as mad’u (object of da'wah). This is conducted by the teacher as a da’i or preacher (the subject of da’wah, social communicator and guide). Social counseling is a field of social life service for students, which helps students assess and build an effective and healthy social relationship with their peers or with the wider social environment. Social counseling is a field service required to help students adjust themselves in school, in this case the students’ relationships with students and teachers in school. Da’wah communication is used to deliver the kind of service appropriate to the student’s social counseling; such as the introduction of the school environment, curriculum, teacher characteristics, so that students do not have difficulties in adapting to the social environment in school.